Biological control of the native endophytic fungus Pochonia chlamydosporia from the root nodule of Dolichos lablab on Fusarium wilt of banana TR4 - Zhou, Yunfan; Yang, Limei; Xu, Shengtao; Li, Shu; Zeng, Li; Shang, Hui; Li, Xundong; Fan, Huacai; Zheng, Sijun (Frontiers Media, 2024)
Fusarium wilt of banana caused by Fusarium oxysporum f. sp. cubense , Tropical Race 4 (TR4) is a soil-borne disease, and it is devastating. At present, the biological control using antagonistic microorganisms to mitigate TR4 is one of the best strategies as a safe and green way. Yunnan has abundant and diverse microbial resources. Using the dual-culture method, the antagonistic endophytic fungi against TR4 were isolated and screened from the root nodule of Dolichos lablab . The effect of the highest antagonistic activity strain on the morphology of the TR4 mycelium was observed using the scanning electron microscope. According to morphological characteristics and sequence analysis, the strain was identified. The biocontrol effect and plant growth promotion were investigated by greenhouse pot experiment. Using the confocal laser scanning microscope and the real-time fluorescence quantitative PCR, the dynamics of TR4 infestation and the TR4 content in banana plant roots and corms would also be detected. In this study, 18 native endophytic fungi were isolated from a root nodule sample of Dolichos lablab in the mulch for banana fields in Yuxi, Yunnan Province, China. The YNF2217 strain showed a high antagonistic activity against TR4 in plate confrontation experiments, and the inhibition rate of YNF2217 is 77.63%. After TR4 culture with YNF2217 for 7 days in plate confrontation experiments, the morphology of the TR4 mycelium appeared deformed and swollen when observed under a scanning electron microscope. According to morphological characteristics and sequence analysis, the strain YNF2217 was identified as Pochonia chlamydosporia . In the greenhouse pot experiment, the biocontrol effect of YNF2217 fermentation solution on TR4 was 70.97% and 96.87% on banana plant leaves and corms, respectively. Furthermore, YNF2217 significantly promoted the growth of banana plants, such as plant height, leaf length, leaf width, leaf number, pseudostem girth, and both the aboveground and underground fresh weight. Observations of TR4 infestation dynamics in banana roots and corms, along with real-time fluorescence quantitative PCR, verified that YNF2217 inoculation could significantly reduce the TR4 content. Therefore, YNF2217 as P. chlamydosporia , which was found first time in China and reported here, is expected to be an important new fungal resource for the green control of Fusarium wilt of banana in the future.